2021
DOI: 10.1177/03635465211041582
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cell Sheets Improve Early Biomechanical Graft Strength in Rabbits After Anterior Cruciate Ligament Reconstruction

Abstract: Background: Although various reconstruction techniques are available for anterior cruciate ligament (ACL) injuries, a long recovery time is required before patients return to sports activities, as the reconstructed ACL requires time to regain strength. To date, several studies have reported use of mesenchymal stem cells in orthopaedic surgery; however, no studies have used adipose-derived stem cell (ADSC) sheets in ACL reconstruction (ACLR). Hypothesis: ADSC sheet transplantation can improve biomechanical stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Matsumoto et. al., [114] had similar findings indicating improved early biomechanical strength and tendon-bone healing. In their study they also used a rabbit model undergoing ACLR with ST autograft.…”
Section: Adipose Derived Stem Cells (Adscs)mentioning
confidence: 63%
“…Matsumoto et. al., [114] had similar findings indicating improved early biomechanical strength and tendon-bone healing. In their study they also used a rabbit model undergoing ACLR with ST autograft.…”
Section: Adipose Derived Stem Cells (Adscs)mentioning
confidence: 63%
“…41 The same group later showed that BMP 2–transduced ACL-derived CD34 + cells further improved graft osteointegration and tensile strength of the reconstructed complex. 25 Cell sheets formed by adipose-derived stromal cells 39 were also reported to improve the biomechanical strength of the reconstructed complex at the early stage after ACLR. Although these cell sheets all showed regenerative capacity, ligament-derived stem cells/TDSCs showed high proliferation, clonogenicity, and multilineage differentiation potential, including ligamentous/tenogenic differentiation potential, and hence may have better potential for tendon and tendon-bone junction repair.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the biocompatibility of scaffolds and inhomogeneous injection of cells, the cell sheet approach is developing rapidly. 25,39,41 The connective tissue growth factor and ascorbic acid–treated tendon-derived stem cell (TDSC) sheet has been shown to promote tendon healing after acute injury and graft healing after ACLR in animal models. 37,38 However, the need to maintain cell viability and stability and the potential uncontrolled actions of transplanted cells are key issues to be solved for the clinical translation of all stem cell–based therapies.…”
mentioning
confidence: 99%
“…In preclinical studies, osteoinductive factors, such as bone morphogenetic protein-2 (BMP-2) ( Crispim et al, 2018 ), α-fibroblast growth factor (α-FGF) ( Lu et al, 2018 ), basic fibroblast growth factor (bFGF) ( Kimura et al, 2008 ), granulocyte colony-stimulating factor (G-CSF) ( Sasaki et al, 2008 ), and transforming growth factor-β1 (TGF-β1) ( Yamazaki et al, 2005 ) enhanced tunnel bone formation and, hence, promoted tendon graft-to-bone tunnel healing after ACLR ( Table 2 ). Besides, cells like ACL-derived CD34 + cell ( Mifune et al, 2012 ; Mifune et al, 2013 ), tendon-derived stem cells (TDSCs) ( Lui et al, 2014c ), bone marrow-derived MSCs (BMSCs) ( Hur et al, 2019 ), and adipose-derived stem cells (ADSCs) ( Matsumoto et al, 2021 ) had been applied directly or made into cell sheets for the enhancement of bone formation after ACLR. These cells could release osteogenic factors and promote osteogenesis at the graft–bone interface.…”
Section: An Inductive Approach For Developing New Biologics For Improving Graft Healingmentioning
confidence: 99%